A Comparative Consideration of Innovative Digital Teaching/Learning Methods Pre-and Post-Pandemic in Two Universities in Italy and Nigeria - Tewo V. Bakare; Helen Opara; Concetta Tino; Monica Fedeli (Universidade de Lisboa, 2022)
This paper presents a descriptive analysis and comparison of higher education policies at the State and organisational levels, methods and effectiveness of digital learning in Italy and Nigeria due to the changes occasioned by the COVID-19 pandemic. It is a reflection of the Adult Education Academy (AEA) 2021 experience that was focused on the consideration of the status pre-and post-pandemic along the mega, meso and micro dimensions in a bid to create an optimal learning environment, encourage innovative teaching methods in both countries and learn lessons. From a comparative perspective, the purpose of this paper is to explore the practices and strategies implemented by the two universities in Italy and Nigeria to address the challenges caused by the pandemic. Some practical teaching/learning methods will be proposed to prepare institutions for the new normal.